(untitled) (The International Research Journal of Management Science, 2024)
Purpose: The major goal of the study was to examine the effect of dimensions of digital marketing such as social media marketing, email marketing, and mobile marketing on consumer purchasing behaviour towards consumer apparel. Methods/Design: Six-point Likert scale structured questionnaire was utilized for the collection of primary data. The study’s population was consumers of consumer apparel in Nepal. The sample size was 385 consumer apparel users. A convenient sampling method was used in the study. A causal effect research design was used for the research. Regression analysis was used to identify the effect of independent variables on purchasing behaviour. Findings: The result of the study showed that social media marketing and mobile marketing have a strong significant role in the development of purchasing behaviour but there is not any significant effect of email marketing in the development of purchasing behaviour in Nepal. Conclusions: It is concluded that social media marketing and mobile marketing have significant roles in the development of consumer buying behaviour and can lead to an increase in consumer buying behaviour, but email marketing does not have any role in shaping consumer buying behaviour. Recommendation: Based on some limitations of the study, the variables that are not captured in the study can be used. This research can also be done on other products, like smartphones, laptops, motorcycles, and other service industries. Demographic variables can be used as moderating variables in this model. Originality/Value: This study is useful for consumer apparel sellers. By understanding factors affecting digital marketing on purchasing behaviour, the sellers can improve their business strategies. The study also suggests that marketers should consider mobile marketing and social media marketing to increase the sales of consumer apparel. The study’s findings offer a guide for future researchers and policymakers regarding consumer apparel.